Evaluation of cerebrospinal fluid treponema pallidum particle agglutination assay titer for neurosyphilis diagnosis among HIV-negative syphilis patients - Shi, Mei; Long, Fuquan; Zou, Danyang; Gu, Xin; Ni, Liyan; Cheng, Yuanyuan; Qi, Tengfei; Zhao, Wei; Zhu, Lin; Guan, Zhifang; Zhou, Pingyu (Frontiers in Immunology, 2025)
PurposeThe study aimed to assess the association between CSF-TPPA titer and the presence of neurosyphilis, and to determine the optimal CSF-TPPA titer cutoff for diagnosing neurosyphilis.MethodsWe conducted a cross-sectional study at a single center from April 2020 and January 2022.Receiver operating characteristic (ROC) analysis was used to assess the performance of CSF-TPPA titer in the diagnosis for neurosyphilis. The relationship between CSF-TPPA titer and neurosyphilis was investigated by restricted cubic spline (RCS) curves.ResultsA total of 715 HIV-negative syphilis patients were included in the final analysis. CSF-TPPA was reactive in 443 cases (62.0%), with a median titer of 1:160 (IQR, Negative to 1:2560). The area under curve (AUC) of CSF-TPPA titer was 0.967 (95% Confidence interval (CI): 0.951- 0.979). CSF-TPPA titer ≥ 1:320 provided a sensitivity of 92.53% and a specificity of 87.96% for the identification of neurosyphilis. For those presumptive neurosyphilis patients, CSF-TPPA ≥1:320 could effectively identified symptomatic neurosyphilis. The RCS curve revealed a non-linear and positive association between CSF-TPPA titer and risk of neurosyphilis. After full adjustments for confounding covariates, it showed that the prevalence of neurosyphilis was relatively flat until CSF-TPPA titer reached 1:320 and then started to escalated rapidly afterwards.ConclusionThis study revealed that a CSF-TPPA titer ≥ 1:320 can be used as a highly sensitive and practical marker for diagnosing neurosyphilis. A titer threshold of ≥1:320 could offer a reliable alternative in cases when CSF-VDRL is negative.